Synthesis and Structural Elucidation of Substituted s-Triazines - Deshmukh, A.Y.; Rathod, D.B.; Tayade, D.T.; Bhagwatkar, R.A.; Patil, S.U. (Asian Journal of Chemistry, 2010)
2-Amino-4-hydroxy-s-triazine was synthesized by the interaction of cyanoguanidine with formic acid. On further reaction with various isothiocyanate in acetone-ethanol medium to produce 1-(4-hydroxy)-s-triazino-3-substituted thiocarbamide (III). The products synthesized in these reactions were characterized on the basis of conventional elemental analysis, chemical characteristics and through IR and NMR spectral analysis.